Sudan tarihi (17. ve 18. yüzyıllar) üzerine yapılan çalışmalar : sistematik literatür incelemesi - Öner, Muhammed Fatih (My University, 2025)
Bu tez, Sudan’ın 17. ve 18. yüzyıllar arasındaki tarihî ve kültürel geçmişini, etnik kimliklerini, dinî dinamiklerini ve toplumsal değişimlerini ele alan eserleri sistematik literatür incelemesine tâbi tutmaktadır. Çalışma, literatür taraması yoluyla mezkûr zaman aralığına dair eserler üzerinden sahada mevcut çalışmaları ortaya koymaktadır. Türkçe, İngilizce ve Arapça eserlerin analiz sonuçlarında; Sennar, Kordofan, Darfur bölgeleri özelinde “Func Sultanlığı” döneminin yoğun şekilde işlendiği, geç veya modern “Sudan Devleti” kavramının yer almadığı tespit edilmektedir. Ortak atıf analizinde ise kitaplar arasında en çok atıf yapılan kaynağın Func kronikleri ve bazı Batılı seyyahlar olduğu görülmektedir. Araştırmanın amacı, Sudan’ın 17. ve 18. yüzyıllardaki dinî, siyasi, toplumsal ve kültürel dönüşümünün anlaşılabilmesine, modern Sudan’ın inşasındaki tarihsel dinamiklerin daha iyi kavranabilmesine yönelik çalışmalara zemin oluşturabilmek, literatürdeki boşlukları ve sorunlu alanları tespit edebilmektir. Aynı zamanda, Sudan tarihi hakkındaki çalışmalara dair yapılan tespit ve analizlerle, günümüzde gerek Afrika’da gerekse küresel bağlamda yaşanan gelişmelerin değerlendirilmesine olumlu katkılar sunabilmektir.

This thesis conducts a systematic literature review of works examining Sudan's history, cultural structures, ethnic identities, religious dynamics, and social changes between the 17th and 18th centuries. It investigates the influence of Muslim Arabs, Egypt/ Turkish-Ottoman, and British powers on Sudan, as well as socio-political factors such as local sultanates (the Funj Sultanate in Sennar, the Fur Sultanate, the Keira Sultanate in Darfur, the Takali Sultanate in South Kordofan, Dar Mesalit on the ChadSudan border, and other sultanates) and trade, all of which played a role in shaping Sudan. The study aims to present existing works in the field through a literature review of works related to this time period. The analysis of Turkish, English, and Arabic sources reveals that the Funj Sultanate period is most heavily addressed in the Sennar, Kordofan, and Darfur regions, and that the concept of the later or modern Sudan State is notably absent. The common citation analysis reveals that the most frequently cited sources are the Funj Chronicles and certain Western travelers. This thesis is also important for understanding the religious, political, social, and cultural transformation processes in Sudan during the 17th and 18th centuries, as well as for grasping the historical dynamics involved in the construction of modern Sudan. Understanding Sudan's identity structures and social dynamics will not only help us better comprehend developments in Africa, but also global crises and foreign policy practices. Furthermore, the thesis aims to contribute to regional historiography by filling gaps in the literature on Sudan's historical processes. It is expected to provide a framework that will facilitate deeper research into Sudan.
Keywords: 17. yy; 17th century; 18. yy; 18th century; Abyssinia; Africa; Afrika; Arab; Arap Sudan; Christianity; Colonialism; Darfur; Egypt; England; Func; Funj; Fur; Habeşistan; History; Hristiyanlık; Islam; İngiltere; İslam; Mısır; Missionary; Misyonerlik; Osmanlı; Ottoman; sömürgecilik; Sudan; Sudan History; Sudan Tarihi; Tarih